Oblique Politics and Esotericism in Michael Psellos - Arabatzis, Georges (Peitho. Examina Antiqua, 2016)
The paper examines the relation of esotericism and oblique politics in the Byzantine philosopher Michael Psellos (11th century) on the basis of Eva De Vries’ study of the letters that Psellos addressed to the statesman Leo Paraspondylos. Traditionally, the name of Psellos signifies a revival of Neoplatonism in medieval Constantinople according to researchers like Chr. Zervos in the beginning of 20th century. Contemporary researchers such as Anthony Kaldellis and Stratis Papaioannou point to a more organic than speculative theorization in Psellos’ work while another contemporary scholar, Frederick Lauritzen, undertakes a synthesis of the two approaches. In any case, as this paper supports, it would be inadequate to consider the relation of esotericism to politics without referring to the evolution of the moral standards considered in a contextualized manner.